Employee Perspectives on Professional Growth: A Qualitative Study of Human Resource Development Initiatives - Sirojudin, Muhammad; Wijoyo, Tuwuh Adhistyo (PT. Banjarese Pacific Indonesia, 2024)
This research examines the perspectives and experiences of workers about Human Resource Development (HRD) programs in order to determine the aspects that influence engagement, satisfaction, and overall effectiveness. Employing a qualitative methodology, the study included semi-structured interviews and focus groups with personnel from several departments. The results indicate that HRD programs are most efficient when they are congruent with individuals' specific career objectives and professional requirements, and when they have sufficient organizational resources and management support. The identification of challenges such as program rigidity and lack of relevance emphasizes the need for HRD methods that are more flexible and responsive. The research highlights the need of customizing HRD programs to cater to the varied requirements of employees and adjusting to rapid changes in the work environment. The findings provide practical and effective guidance for firms to improve their HRD processes and give stronger support for employee development. Further investigation is recommended to examine the incorporation of emerging technologies in HRD and evaluate their influence on employee engagement and development.